Pluralism, equality, and identity : comparative studies - Oommen, T K. (New Delhi : New York : Oxford University Press, 2002)
With reference to Europe and South Asia.
Includes bibliographical references (p. [174]-181) and indexes.
Keywords: Cultural pluralism -- India; Cultural pluralism -- Europe; Comparative government; National characteristics; Equality